Myths about fingerprint evidence: Basic facts countering miscarriage of justice. Part 2 - Mansour, Saleh; Zade, Shital; Rohatgi, Shipra; Oklevski, Slobodan (Wydawnictwo Uniwersytetu Wrocławskiego, 2021)
This is the second part of the study that aims at highlighting twenty-four myths about fingerprint evidence. In this paper, the authors are going to explicate and clarify the difference between the scientific facts and the wrongful concepts that negatively affect the justice system and the effective usage of fingerprint evidence starting from the initial investigation at the crime scene until the final trial at the courtroom.
Keywords: starzenie się odcisków palców; składniki; anatomia skóry; techniki przetwarzania; delikatne powierzchnie; wrażliwość odcisków palców; interpretacja dowodów; metodologia ACE-V; AFIS (Automatyczny System Identyfikacji Daktyloskopijnej)